Influence Of Social Media Marketing Strategies Towards Learning Interests Of Hospitality Students At Star International Hotel School - Iin Fetiani; Ni Putu Widhia Rahayu (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this research is to find out the influence of social media marketing strategies on students' interest in learning at Star International Hotel School. The sample for this research is 100 respondents calculated using accidental sampling. This research uses quantitative methods using IBM SPSS 25. Based on the research results, it is known that social media marketing strategies have a positive and significant effect on interest in learning. This research is expected to help Star International Hotel School in increasing students' interest in learning by continuing to innovate in creating marketing and content strategies. content in social media.